Awareness of the Psychological Bias of Naïve Realism Can Increase Acceptance of Cultural Differences. (June 2022) - López-Rodríguez, Lucía; Halperin, Eran; Vázquez, Alexandra; Cuadrado, Isabel; Navas, Marisol; Gómez, Ángel
Acceptance of cultural differences can contribute to diversity. However, naïve realism—the conviction that one's views are objective whereas others' are biased—might hinder intercultural coexistence. We tested, in three experimental studies, whether a cognitive strategy based on raising awareness of the naïve realism, without any reference to culture and free of emotional involvement, can have a beneficial effect on cultural acceptance. Results revealed that participants showed more acceptance of cultural differences once they were aware of this bias (Study 1). The intervention had an indirect effect on acceptance via openness, especially for participants higher in prejudice (Study 2). Participants aware of this bias could not maintain an enhanced self-view, which mediated the effect of the manipulation on acceptance (Study 3). These findings suggest that strategies based on "cold" cognition, without an explicit emphasis on culture, might be beneficial for increasing the acceptance of cultural differences in an era of xenophobia.